Line Balancing Analysis of Tuner Product Manufacturing - Sihombing, Haeryip (Engg Journals Publications, 2011)
The processing time and the number of operators have strong relationship with the productivity of production lines. In the tuner production line, three significant factors related to productivity through using of line balancing method are the number of operator, production tools/equipment, and production process. This study performed the line balancing method through simulation model in order to reduce the line unbalancing causes and relocate the workforce associated to idle time, eliminating the bottleneck, and at the same time maintaining/ improving the productivity. To analyze the production line, we use a develop simulation tool, called Fact-Model, to modeling the production line (with the graph of critical path network and working time) and the works estimated (related to the cycle time, takt time, non-value added activities, quantity, and cost). Fact-Model is facilitated with the features that enable the user to depict the real production flows by using their owned real pictures/photos taken into their simulation model.